Dual fluoroscopic evaluation of human tibiofemoral joint kinematics during a prolonged standing: A pilot study - Sabri Uzuner; Marcel L. Rodriguez; LePing Li; Serdar Kucuk (Engineering Science and Technology, an International Journal, 2019)
A complete knowledge of tibiofemoral joint kinematics is essential for understanding the function of the healthy and pathological joint. The objective of the present study was to establish a dual fluoroscopic measurement protocol and a data processing approach for the creep response of the knee joint in order to further evaluate the mechanical properties of articular cartilage and meniscus in vivo. A computational approach was developed for the determination of 3D translations and rotations of the joints of young participants with no history of injury using dual fluoroscopic images of loaded joints and joint geometry reconstructed from magnetic resonance imaging of the unloaded joints. High-resolution X-ray images were obtained for the distal femur and proximal tibia during 10-min standing when approximately ¾ body weight was slowly applied to the right leg and then kept constant for the rest duration of the test. Anatomic coordinate systems were established for the 3D models of distal femur and proximal tibia. Translations and rotations of the joint as functions of time were then evaluated using the X-ray images and these coordinate systems with the JointTrack software. The displacements in the proximal-distal direction obtained from two participants were consistent, showing a substantial increase in the initial phase when joint loading increased from nil to ¾ body weight and a continued small increase over time while the joint loading remained constant. The maximum anterior-posterior translations during 10-min standing were approximately 4 mm for both participants, although one showed better stability than the other. In conclusion, a creep loading protocol of the knee joint can be reasonably established for in vivo conditions and evaluated with the image-based computational approach. Keywords: Creep, In vivo study, Knee joint kinematics, Dual fluoroscopy, Magnetic resonance imaging, Image-based computer model